Analysis of genetic variants in the 5’ regulatory region of the ALAS1 gene in South African patients with Variegate Porphyria (VP) - Du Plessis, Nelita (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Genetics))—University of Stellenbosch, 2007.